Multiblock microstructure using a binary system of metallocene catalysts with diethyl zinc as transfer agent - Pereira, Leticia; Martins, Roberto; Marques, Maria (Lviv Polytechnic Publishing House, 2013)
The aim of this study was to synthesize ethylene-hexene copolymers of the type LLDPE using a combination of metallocene binary catalysts (Cat 1:Cp2ZrCl2 and Cat 2:Et(IndH4)2ZrCl2), where each catalyst has different microstructural control capacities. The effect of diethyl zinc (DEZ) concentration as a chain shuttling agent (CSA) was evaluated in parameters such as catalytic activity, as well as thermal properties, comonomer content incorporated into the polymer chain, crystal structure, and also dynamic mechanical properties of the obtained copolymers. The results showed that, opposite to the behavior of the catalyst mixtures, DEZ promoted an increase in the polymerization activity with the isolated catalysts. Furthermore,CSA provided the increase of the rigid segments in the copolymer chain obtained with the binary catalyst. Синтезовано етилен-гексен кополімери типу LLDPE, використовуючи комбінацію металлоценових бінарних каталізаторів (Кat 1: Cp2ZrCl2 і Кat 2: Et (IndH4)2ZrCl2), де кожен каталізатор має різні можливості контролю мікроструктури. Проведено оцінювання ефекту діетилцинку (ДЕЦ) як ланцюгового човникового агента (ЛЧА) стосовно таких параметрів, як каталітична активність, теплових властивостей, вміст комономеру, включеного до полімерного ланцюга, кристалічної структури, а також динамічних механічних властивостей отриманих кополімерів. Показано, що на відміну від суміші каталізаторів, ДЕЦ сприяє збільшенню активності полімеризації з ізольованими каталізаторами. ЛЧА збільшує жорсткість сегментів в кополімерному ланцюзі, отриманих за участю подвійного каталізатора.
Мультиблочна мікроструктура з використанням подвійної системи металлоценових каталізаторів з діетиловим цинком як агенту переносу
Keywords: polyethylene; ethylene copolymer; chain shuttling agent; binary catalyst; metallocene; поліетилен; кополімер етилену; човниковий ланцюговий агент; бінарний каталізатор; металлоцен